2019
DOI: 10.1016/j.bbr.2019.112106
|View full text |Cite|
|
Sign up to set email alerts
|

Early intervention with ABA prevents neuroinflammation and memory impairment in a triple transgenic mice model of Alzheimer´s disease

Abstract: Highlights• Abscisic Acid (ABA) treatment can effectively prevent memory impairment in a murine model of Alzheimer disease (AD). • ABA treatment can prevent microglia transition to inflammatory state in transgenic model of AD.• The beneficial effects of ABA, PPARᵧ agonist and an insulin sensitizer in the central nervous system are independent of peripheral insulin resistance. • Further studies will establish whether later intervention (when the disease may be in initial stages), but longer treatments can guara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…was assessed by novel object recognition (NOR) test. NOR experiment was conducted as described [46]. On the test day, the subjects were left to explore two identical objects for 10 min (familiarization phase).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…was assessed by novel object recognition (NOR) test. NOR experiment was conducted as described [46]. On the test day, the subjects were left to explore two identical objects for 10 min (familiarization phase).…”
Section: Methodsmentioning
confidence: 99%
“…For the quantification of Iba1 labeling, we used 20×lens. Image J software combined with FracLac plugin [51] was used to analyse the microglia morphology in sections from sham and 6-OHDA groups of both females and males as previously described [46]. The microglia morphological parameters that were analysed were (1) cell area , meaning the total number of pixels corresponding to the area occupied by the cell, soma, and branches; and (2) cell perimeter , based on the single outline cell shape.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we have demonstrated that ABA can improve memory in an animal model of AD, reducing neuroinflammatory markers and restoring insulin-mediating molecule expression [101][102][103]. To our knowledge, ABA has not yet been tested in clinical trials.…”
Section: Nutraceuticals As a Treatment Of Admentioning
confidence: 99%
“…Accumulated evidence from preclinical [ 10 ] and clinical trials have demonstrated that early intervention with multimodal intervention (exercise, diet, and cognitive training) [ 11 , 12 ] and/or probiotics [ 13 ] can satisfactorily delay the progress from mild cognitive impairment (MCI) to dementia. Thus, early risk prediction is crucial for health care providers to initiate effective prevention interventions, even starting decades before the first symptoms appear.…”
Section: Introductionmentioning
confidence: 99%